AGING AND PUBLIC POLICY: SHAPING INCLUSIVE HEALTHCARE SYSTEMS FOR THE ELDERLY IN GIANYAR REGENCY, BALI - Wijaya, Made Indra (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
The rapid aging of the global population presents significant challenges for public policy, requiring comprehensive strategies to meet the diverse needs of the elderly. This study focuses on the elderly population in Gianyar Regency, Bali, analyzing their healthcare access, usage patterns, obstacles, and satisfaction levels. The research aims to assess healthcare access and utilization among the elderly, identify barriers they face, and evaluate their satisfaction to inform the development of inclusive health policies. A cross-sectional study was conducted with 500 elderly participants from various sub-districts in Gianyar Regency. Data were collected through structured interviews and surveys, covering demographics, healthcare access, utilization, barriers, and satisfaction. Descriptive and inferential statistics were employed for analysis. Most elderly individuals prefer community health centers (puskesmas) for healthcare, citing trust and accessibility. However, transportation, financial constraints, and mobility issues hinder regular visits. A significant correlation was found between demographic factors (age, gender, living arrangements) and healthcare access and satisfaction. Elderly individuals living alone often delay or avoid seeking care due to limited support. High satisfaction with puskesmas highlights their key role in elderly care. The findings align with regional trends in Southeast Asia and offer insights for policymakers. Addressing barriers and enhancing puskesmas services can improve healthcare for the elderly in Gianyar and similar regions. Policymakers should focus on expanding puskesmas, improving transportation, and strengthening financial support to ensure accessible and inclusive healthcare for the elderly, promoting healthy aging.